Developing homestay to support community-based tourism - Ilham Junaid; Nur Salam; Muh. Arfin M. Salim (Masyarakat, Kebudayaan dan Politik, 2019)
Wakatobi regency has been chosen as a ten-top priority tourism destination in Indonesia. It provides the opportunity for the local community to obtain benefits through tourism. The aims of this research are 1) to study the expectation of the community related to the management of homestay as accommodation business; 2) to analyse challenges and provide recommendations concerning how to implement community-based tourism on the perspective of community as the organiser of the homestay. Qualitative research conducted in March 2018 by visiting Wakatobi for participant observation and interviews three community members or homestay managers, two tour guides and two people from the tourism industry (accommodation). The research indicates that tourism has encouraged the local community to manage homestay, although there are members of the community require motivation and support to understand the significances of managing homestay and tourism. The management of homestay by the local community links to the implementation of community-based tourism and to optimise the management of homestay; it is necessary to provide sustainable training for the local community as well as to empower people through local tourism organisation. Key attractors such as activities and alternative attractions for the visitors are essential for the management of homestay. Limited numbers of tourists who choose homestay to become the challenge for homestay management, thus, the local community expects that the increasing number of tourists as well as a willingness by tourists to choose homestay as their accommodation.